The effect of hearing ability on dual-task performance following multi-domain training in older adults with mild cognitive impairment: findings from the SYNERGIC trial. - Downey, Rachel I.; Petersen, Berkley J.; Mohanathas, Niroshica; Campos, Jennifer L.; Montero-Odasso, Manuel; Bherer, Louis; Pichora-Fuller, M. Kathleen; Bray, Nick W.; Burhan, Amer M.; Camicioli, Richard; Fraser, Sarah; Liu-Ambrose, Teresa; et al. (Frontiers in Aging Neuroscience, 2026)
Background: Hearing loss is one of the largest potentially modifiable risk factors for dementia and is linked with poor cognitive-motor dual-task performance (e.g., walking while performing a cognitive task). Hearing loss is more prevalent and severe in males, whereas dementia is more prevalent in females. Physical exercise and cognitive interventions appear promising in improving dual-tasking in older adults; however, it is currently unclear whether hearing ability affects training efficacy on dual-task outcomes in older adults with mild cognitive impairment (MCI), and whether sex influences this effect. Objective: The primary aim of this study was to examine whether hearing ability affects dual-task performance at baseline and after training in individuals with MCI, and whether sex further influences these relationships, irrespective of intervention arm. Methods: Secondary data was analysed from 75 participants with MCI (Mage = 73.66 ± 6.67) enrolled in the SYNERGIC trial. Hearing ability was assessed using self-report and behavioral measures. Participants completed a 20-week intervention: (1) Exercise (aerobic-resistance exercise + sham cognitive training; n = 31), (2) Multi-Domain Training (aerobic-resistance exercise + cognitive training; n = 32), or (3) Placebo Training (balance and toning exercises + sham cognitive training; n = 12). Primary outcomes included dual-task gait and cognitive performance. Results: At baseline, poorer hearing predicted worse dual-task performance, particularly in males. Dual-task gait variability significantly improved following Multi-Domain Training in participants with a greater degree of self-reported hearing complaints. Sex-stratified analyses revealed that females with more hearing complaints improved more across all interventions, while in the Multi-Domain group, males with poorer objective hearing and females with better hearing showed the greatest gains. Additionally, in those with poorer hearing, lower cognitive scores (MoCA) predicted greater improvements after Multi-Domain Training, but a decline after Placebo Training. Conclusion: Hearing ability, sex, and cognitive status appear to interact to influence the effects of exercise and cognitive training on dual-task performance in older adults with MCI. Multi-Domain Training appears particularly beneficial for those with hearing loss (who are male and/or have lower cognitive status), highlighting the need for personalized interventions to preserve function and slow decline in this at-risk population. Clinical trial registration: https://www.clinicaltrials.gov/ct2/show/NCT02808676, NCT02808676.